Jewish experiences across the Americas : local histories through global lenses - Rac, Katalin Franciska; Ureña Valerio, Lenny A., 1977- (University of Florida Press, 2022)
"This volume explores the local specificities and global forces that shaped Jewish experiences in the Americas across five centuries, illuminating the culturally, religiously, and politically diverse lives of Jewish minorities in the Western Hemisphere"--